Which economic model for mobile payments? - Laetitia Chaix; Dominique Torre (International Telecommunications Society (ITS), 2012)
This paper explores the economic models associated to different mobile-payment systems. We first present the existing experiences and review the few economic literature on the subject. We then concentrate on the four economic models currently experimented around the world: the operator-centric model, the bank-centric model, the collaborative model, and the independent service provider model. We select relevant cases of recent development of these models and we try to present them in an appropriated theoretical settings. We find that their fundamental components make them viable systems, able to improve without ambiguity the transaction technology in different economic environments. These models have however different advantages and limits. If we limit the analysis to quite large distant payments, the operator-centric model is adapted to emerging countries without a banking system sufficiently dense, with users making a relative few number of relatively large distant payments. The bank-centric could have been more adapted to professional users in countries with a fully developed financial environment. These characteristics are also observed for the two others models. The independent service provider (ISP) model seems now the main competitor of the bank-centric model. The structure of the costs and the technology of this model, out of the control of operators (and partly from banks) seem more adapted for users making many payments in a secure and developed economic area. Despite difficulties to define precisely its structure of governance, the collaborative model can also compete with the operator centric one in a non fully bancarized environment. We finally discuss the results and compare the potentiality of the four models.
Keywords: E42; O33; 330; Electronic Payment; Mobile Payment; Business Models; Network Externalities.